60.7.110 problem 1701 (book 6.110)

Internal problem ID [11699]
Book : Differential Gleichungen, E. Kamke, 3rd ed. Chelsea Pub. NY, 1948
Section : Chapter 6, non-linear second order
Problem number : 1701 (book 6.110)
Date solved : Monday, January 27, 2025 at 11:30:14 PM
CAS classification : [[_2nd_order, _missing_x], [_2nd_order, _reducible, _mu_x_y1]]

\begin{align*} y^{\prime \prime } y-{y^{\prime }}^{2}+1&=0 \end{align*}

Solution by Maple

Time used: 0.087 (sec). Leaf size: 59

dsolve(diff(diff(y(x),x),x)*y(x)-diff(y(x),x)^2+1=0,y(x), singsol=all)
 
\begin{align*} y &= \frac {c_{1} \left (-{\mathrm e}^{\frac {x +c_{2}}{c_{1}}}+{\mathrm e}^{\frac {-x -c_{2}}{c_{1}}}\right )}{2} \\ y &= -\frac {c_{1} \left (-{\mathrm e}^{\frac {x +c_{2}}{c_{1}}}+{\mathrm e}^{\frac {-x -c_{2}}{c_{1}}}\right )}{2} \\ \end{align*}

Solution by Mathematica

Time used: 14.055 (sec). Leaf size: 84

DSolve[D[y[x],{x,2}]*y[x]-D[y[x],x]^2+1==0,y[x],x,IncludeSingularSolutions -> True]
 
\begin{align*} y(x)\to -\frac {\sinh \left (\sqrt {e^{2 c_1}} (x+c_2)\right )}{\sqrt {e^{2 c_1}}} \\ y(x)\to \frac {\sinh \left (\sqrt {e^{2 c_1}} (x+c_2)\right )}{\sqrt {e^{2 c_1}}} \\ y(x)\to -x-c_2 \\ y(x)\to x+c_2 \\ \end{align*}